Strategic Integration of AI Monitoring Frameworks in Business Contexts: a Multisectoral Case Study Analysis - Sau, Ayan; Chandrasekhar, Varun (Global journal of Business and Integral Security, 2026)
The integration of Artificial Intelligence (AI) into enterprises has reshaped strategy, governance, and compliance. As AI systems grow in autonomy, scalable frameworks are needed to monitor performance, fairness, and ethics. This paper proposes a business-aligned monitoring model informed by case studies in finance, human resources, and policy governance, drawing on the Big 5 consulting firms—Deloitte, EY, KPMG, PwC, and McKinsey. Grounded in socio-technical systems theory, Technology Readiness Levels (TRLs), and ethics readiness models, the framework addresses performance tracking, bias mitigation, and ethical oversight. Findings show that embedding fairness and ethics strengthens compliance, reduces risk, and builds stakeholder trust. We present a roadmap for enterprise-wide AI governance that emphasizes continuous auditing and cross-functional collaboration. AI monitoring is a core driver of responsible innovation.